2013
DOI: 10.1007/978-3-319-02675-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Spaces, Sharing Lives – The Impact of Robot Mobility on User Perception of a Home Companion Robot

Abstract: This paper examines the role of spatial behaviours in building human-robot relationships. A group of 8 participants, involved in a long-term HRI study, interacted with an artificial agent using different embodiments over a period of one and a half months. The robot embodiments had similar interactional and expressive capabilities, but only one embodiment was capable of moving. Participants reported feeling closer to the robot embodiment capable of physical movement and rated it as more likable. Results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…The results shows higher average ratings for the apologetic TB in comparison to neutral TB in regards to: I felt in company of the TB, TB's recharge behaviour was acceptable, I felt neglected while TB was recharging, The TB was available to interact with me. These preliminary results supports both hypothesis H1, H2 and also conform with earlier long-term HRI studies performed with stationary and moving robots [5]. …”
Section: User Studysupporting
confidence: 92%
“…The results shows higher average ratings for the apologetic TB in comparison to neutral TB in regards to: I felt in company of the TB, TB's recharge behaviour was acceptable, I felt neglected while TB was recharging, The TB was available to interact with me. These preliminary results supports both hypothesis H1, H2 and also conform with earlier long-term HRI studies performed with stationary and moving robots [5]. …”
Section: User Studysupporting
confidence: 92%
“…Autonomous robots may also have an influence on user perception particularly if they are mobile (Cesta et al, 2007;Syrdal et al, 2013) reported that the role of the robot's ability to move and share the physical space with the user affected the formation of human-robot relationships. Lindner and Eschenbach (2013) proposed the idea of social placement for a mobile robot, taking into account affordances while recharging.…”
Section: Related Workmentioning
confidence: 99%
“…Further details about robot house, robot architecture and control systems and experiments with participants in the robot house can be found, for example, in [3,12,16,11,13]. This paper builds on and extends the work described in [18].…”
Section: Related Workmentioning
confidence: 96%
“…[12,16]). One of the robots in the house is the (commercially available) Care-O-bot robot manufactured by Fraunhofer IPA [10].…”
Section: The Robot House and The Care-o-botmentioning
confidence: 99%